Towards Sustainable Tourism in Nepal: An Analysis of Key Opportunities and Challenges - Bhattarai, Utsab (Nepalese Journal of Hospitality and Tourism Management, 2025)
Sustainable tourism is vital for preserving natural resources, enhancing cultural heritage, and promoting economic growth, especially in ecologically rich and culturally diverse countries like Nepal. Nestled in the Himalayas, Nepal is renowned for its stunning landscapes, rich biodiversity, and vibrant culture. However, rapid expansion of tourism has raised concerns about unequal economic benefits, environmental degradation, and cultural erosion. This paper analyses recent literature (since 2010) on sustainable tourism in Nepal using keywords such as “sustainable tourism,” “ecotourism,” “community-based tourism,” and “responsible tourism” across Google Scholar and Scopus. Key themes include tourism development challenges and opportunities, stakeholder engagement, and policy frameworks. Successful initiatives such as Community Forestry and the “Leave No Trace” campaign demonstrate how tourism can support conservation, cultural preservation and local well-being. Despite persistent challenges, Nepal’s focus on community participation and strategic planning shows promise. Nepal can enhance its sustainable tourism framework by fostering collaboration among government, communities, NGOs,and tourists, incorporating global best practices like Costa Rica’s ecotourism model and Bhutan’s high value tourism strategy.